Jesus Research The Gospel of John in Historical Inquiry - Charlesworth, James H. 1940- (London Bloomsbury Publishing PLC, 2019)
Intro -- Title Page -- Copyright Page -- Contents -- List of Abbreviations -- General -- Modern publications -- Hebrew Bible/Old Testament -- New Testament -- Old Testament Apocrypha and Pseudepigrapha -- Dead Sea Scrolls -- Rabbinic Texts -- Apostolic Fathers -- Nag Hammadi Codices -- New Testament Apocrypha and Pseudepigrapha -- Papyri and Ostraca -- Greek and Latin Works -- Notes on Contributors -- Summaries of discussions -- Preface -- Introducing the Focus of the Third Princeton-Prague Symposium: John in Jesus Research -- Why scholars Jettison John in Jesus Research -- Rethinking these reasons to ignore John -- Why John must be used in Jesus Research -- Fascination with the Gospel of John in earlier decades -- Part One: John and the Synoptics in Jesus Research -- Chapter 1: Why the Gospel of John is Fundamental to Jesus Research -- Brief overviews of scholarship -- Johannine and Jesus scholarship today: A paradigm shift in the works -- Perils of using John in Jesus Research: Daunted by the Johannine riddles -- Perils of not using John in Jesus Research: Engaging the Johannine riddles -- Making use of John in the critical quest for Jesus: A call for second criticality -- Conclusion: The Gospels and Jesus in bi-optic perspective -- Chapter 2: Reflections on Matthew, John, and Jesus -- A personal journey -- Some suggestions -- Some clarifications -- The historical Jesus -- Final remarks -- Part Two: Literary and Rhetorical Approaches for Jesus Research in John -- Chapter 3: Some Methodological Considerations Regarding John, Jesus, and History -- The principle: Question of genre -- A test case: Where is Jesus from? -- Another form of historical inquiry: The history of contemporary Judaism -- More on the origins of Jesus -- Implications for the quest for historical data in John
Chapter 4: How and in What Ways Does John's Rhetoric Reflect Jesus' Rhetoric? -- The silent narrator in John, Thucydides, and Plato -- The Johannine Jesus and the historical Jesus: Aphorism in rhetoric -- The Johannine Jesus and the historical Jesus: Rhetoric varies with audience -- Part Three: Johannine Relationships to Early Traditions, Josephus, and Archaeological Data -- Chapter 5: The First Edition of John's Gospel in Light of Archaeology and Contemporary Literature -- Kingly, messianic, and prophetic figures in Josephus in the first century CE3 -- The portrayal of the ministry of Jesus in the first edition of the Gospel of John -- The text of the first edition of the Gospel -- Conclusions regarding the material of the first edition of the Gospel of John -- Chapter 6: John 2:20, "Forty-Six Years": Revisiting J. A. T. Robinson's Chronology of Jesus' Ministry1 -- Robinson's chronology of Jesus' ministry -- The cleansing of the Temple -- "Forty-six years" as a marker for the beginning of Jesus' ministry -- Chapter 7: Historical Tradition in the Fourth Gospel's Depiction of the Baptist -- General considerations -- Connection between John and Jesus -- Overlapping ministries (John 3:22-26) -- John's topography: Bethany (1:28) and Aenon (3:23) -- Synoptic Christology: Witness to Another (1:19-34) -- A uniquely Johannine title: God's lamb (1:29-36) -- Transfer students (1:35-42) -- Conclusion -- Chapter 8: Can Archaeology Help Us See Jesus' Shadows in the Gospel of John? -- Bethzatha: The upper pools of Jerusalem -- The old tendency -- The new insights: Archaeology and John -- Archaeology and the history of Bethzatha -- Pool of Siloam: "The lower pool of Jerusalem" -- The new: Archaeology and John -- Summary -- Conclusion: Symbolism based on history -- Selected Bibliography67 -- Pool of Siloam -- Part Four: Johannine Tendenzen, Theology, and History
Chapter 9: History in John's Portrayal of Jesus -- Growing consensus: "That" and "What" -- The question: "How" and "Why?" -- The paradox: Jesus' words and deeds -- The misunderstanding -- The signs -- Plausible and historical Jesus -- Chapter 10: Jesus and the Historical Implications of John's Temple Cleansing -- John's Temple incident and Jesus Research -- The Johannine account revisited -- The distinctive features of John's Temple incident -- John's Temple incident in the Fourth Gospel's narrative and theology -- Conclusion -- Chapter 11: Jesus of Nazareth in the Gospel of John -- The problem -- The key role of the earthly Jesus -- The problem of wonders -- Jesus speaking in parables -- The testimony7 -- Earthly Jesus in Johannine theology -- Jesus of Nazareth: Fragments of historical evidence -- Jesus of Nazareth -- The story of Jesus of Nazareth -- Jesus of Nazareth as the crucified Messiah and Savior of the world -- Jesus and John the Baptist43 -- Part Five: Summaries of Symposium Discussions -- Chapter 12: Allison, Anderson, Culpepper, and Attridge: Discussion of Papers I -- Chapter 13: Charlesworth and Parsenios: Discussion of Papers II -- Chapter 14: Pokorný, von Wahlde, and Keener: Discussion of Papers III -- Chapter 15: Roskovec, Daise, and a Developing Consensus: Discussion of Papers IV -- Part Six: Appendices -- Notes -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Chapter 11 -- Jesus Research and the Gospel of John: Selected Bibliography -- Modern Author Index -- Scripture Index -- Ancient Sources
Keywords: Jesus Christus; Bibel; Christologie; Aufsatzsammlung